Pedicled iliac bone flap grafting in the treatment of late presentation Legg–Calvé–Perthes disease - Xiao, Yong-bing; Du, Wei; Wu, Pan-feng; Qing, Li-ming; Yu, Fang; Tang, Ju-Yu (Frontiers in Surgery, 2023)
Background: Legg-Calvé-Perthes disease (LCPD) is a juvenile form of ischemic femoral head osteonecrosis affecting children. Severe sequelae will be left in children (especially the older ones) without timely and effective treatment. It is still challenging for clinical management of this disabling disease. The aim of this study was to investigate the clinical and radiological results of patients presenting older than six years and treated with pedicled iliac bone flap grafting for LCPD. Materials and methods: A total of thirteen patients (13 hips) with late presentation of LCPD were treated with pedicled iliac bone flap grafting. Eleven males were identified. The average age of patients was 8.4 years (range 6-13). Preoperational radiographs and pain scores were analyzed for lateral pillar classification and Oucher scale. Final follow-up radiograph was classified using modified Stulberg classification. Limping, extremity length inequality and range of motion of all patients were clinically assessed. Results: The average follow-up of the patients was 70 months (range 46-120). During the surgery, seven hips were found to be lateral pillar grade B, two hips were grade B/C and four hips were grade C. In the final examination, 12 hips were evaluated as good (Stulberg class-I or II) and only one as medium (Stulberg class-III). There was shortening in one patient who was Stulberg class-III. A meaningful difference was detected between the pre-operational and post-operational radiographic values and Ocher scale, regardless of the surgical staging (P<0.05). Conclusions: Pedicled iliac bone flap graft can be used to treat children over 6 years old accompanied by pain with lateral pillar stage B, B/C and C in LCPD.